New and previously known species of Oenonidae (Polychaeta: Annelida) from Lizard Island, Great Barrier Reef, Australia - Zanol, Joana; Ruta, Christine (Zootaxa, 2015)
The family Oenonidae consists of Eunicida species with prionognath jaws. Its Australian fauna had been reported to comprise six species belonging to Arabella, Drilonereis, and Oenone. This study provides descriptions for four new species, redescriptions for three species (two previously recorded and a new record, Drilonereis cf. logani) and diagnoses for the genera recorded from Australia. Currently, eleven species of oenonids, distributed in three genera, are known for the Australian coast. On Lizard Island, this family shows low abundance (19 specimens collected) and high richness (seven species). Our results suggest that despite the increasing accumulation of information, the biodiversity of the family is still poorly estimated.